Enhancing immunotherapy in cancer by targeting emerging immunomodulatory pathways - Kraehenbuehl, Lukas; Weng, Chien-Huan; Eghbali, Shabnam; Wolchok, Jedd D; Merghoub, Taha (Nature reviews. Clinical oncology, 2022)
The discovery and clinical implementation of immune-checkpoint inhibitors (ICIs) targeting CTLA4, PD-1 and PD-L1 has revolutionized the treatment of cancer, as recognized by the 2018 Nobel Prize for Medicine and Physiology. This groundbreaking new approach has improved the outcomes of patients with various forms of advanced-stage cancer; however, the majority of patients receiving these therapies, even in combination, do not derive clinical benefit. Further development of agents targeting additional immune checkpoints, co-stimulatory receptors and/or co-inhibitory receptors that control T cell function is therefore critical. In this Review, we discuss the translational potential and clinical development of agents targeting both co-stimulatory and co-inhibitory T cell receptors. Specifically, we describe their mechanisms of action, and provide an overview of ongoing clinical trials involving novel ICIs including those targeting LAG3, TIM3, TIGIT and BTLA as well as agonists of the co-stimulatory receptors GITR, OX40, 41BB and ICOS. We also discuss several additional approaches, such as harnessing T cell metabolism, in particular via adenosine signalling, inhibition of IDO1, and targeting changes in glucose and fatty acid metabolism. We conclude that further efforts are needed to optimize the timing of combination ICI approaches and, most importantly, to individualize immunotherapy based on both patient-specific and tumour-specific characteristics.